2018
DOI: 10.1155/2018/5456928
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of Drosophila melanogaster to Mancozeb Induces Oxidative Damage and Modulates Nrf2 and HSP70/83

Abstract: Mancozeb (MZ), a manganese- and zinc-containing ethylene-bis-dithiocarbamate, is a broad-spectrum fungicide. Harmful effects of this fungicide have been reported in nontarget organisms via a not fully understood mechanism. Drosophila melanogaster has provided remarkable contributions for toxicological studies. This work was aimed at evaluating the biochemical targets and implication of oxidative stress in MZ-mediated toxicity in drosophilas. Exposure of flies for fifteen days to MZ at 5 and 10 mg/mL through th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 51 publications
(57 reference statements)
1
16
0
Order By: Relevance
“…This is supported by our findings from Table 1, in which the inhibition of GST activity may be due to the increase in the toxicity effect of 1.0% DSS. This increase in the malondialdehyde level agrees with the result of Paula et al (2016), Saraiva et al (2018) and Colpo et al (2018) which showed an increase in the MDA levels of the `Harwich strain of D. melanogaster.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is supported by our findings from Table 1, in which the inhibition of GST activity may be due to the increase in the toxicity effect of 1.0% DSS. This increase in the malondialdehyde level agrees with the result of Paula et al (2016), Saraiva et al (2018) and Colpo et al (2018) which showed an increase in the MDA levels of the `Harwich strain of D. melanogaster.…”
Section: Discussionsupporting
confidence: 92%
“…Thus by taking the sample blank reading, the level of interference is taken into consideration and brought to level zero before other readings are determined (Ingle and Crouch, 1988). Some researchers have determined both the level of malondialdehyde produced from lipid peroxidation (Ohkawa et al, 1979), a standard oxidative damage indicator and level of reactive oxygen species via oxidation of fluorescent dye 2,7-dichlorofluorescein diacetate (DCF-DA) a general index of ROS levels (Pérez-Severiao et al, 2004) using the Harwich strain of D. melanogaster (Paula et al, 2016;Saraiva et al, 2018;Poetini et al, 2018). This is supported by our findings from Table 1, in which the inhibition of GST activity may be due to the increase in the toxicity effect of 1.0% DSS.…”
Section: Discussionmentioning
confidence: 99%
“…melanogaster has been used as a model system for toxicological studies and diseases mechanism such as neurological disorders, cancer, developmental disorders, metabolic and storage disorders and cardiovascular disease (Bier, 2005;Abolaji et al, 2014;Saraiva et al, 2018). In forensic, D.…”
Section: Resultsmentioning
confidence: 99%
“…The groups were composed of 30 individuals. The concentrations used in this study were described by Saraiva et al. (2018) , when MZ decreased in 50 % and 80 % the fly survival and led to a modulation of mRNA steady-state antioxidant enzyme levels with cell stress markers.…”
Section: Methodsmentioning
confidence: 99%
“…This study demonstrates that Drosophila melanogaster is susceptible to MZ when exposed for a prolonged period (15 days). This condition induced mortality and oxidative stress with modulation of the activity and mRNA steady-state levels of antioxidant enzymes ( Saraiva et al., 2018 ). The biochemical mechanisms involved in MZ toxicity are not fully understood.…”
Section: Introductionmentioning
confidence: 99%